Feedback interventions for college alcohol misuse: What, why and for whom? - Walters, Scott T. (2005)
In response to the persistent problem of college drinking, universities have instituted a range of alcohol intervention programs for students. Motivational feedback is one intervention that has garnered support in the literature and been adopted on college campuses. This article reviews published outcome studies that have utilized feedback as a major component of an alcohol intervention for college students. Overall, 11 of the 13 reviewed studies (77%) found a significant reduction in drinking as compared to a control or comparison group. While the studies varied widely in terms of population, follow-up period, and feedback content, it appears that feedback can be effective whether delivered by mail, the Internet, or via a face-to-face motivational interview. Feedback seems to change normative perceptions of drinking and may be more effective among students who drink for social reasons. The addition of a group or individual counseling session does not appear to increase the short-term impact of the feedback.